Structural Insights into BAF47 and BAF155 Complex Formation. Issue 11 (2nd June 2017) - Yan, Li; Xie, Si; Du, Yongming; Qian, Chengmin
Abstract: Mammalian BAF complexes are a subfamily of SWI/SNF ATP-dependent chromatin remodelers that dynamically modulate chromatin structure to regulate fundamental cellular processes including gene transcription, cell cycle control, and DNA damage response. So far, many distinct BAF complexes have been identified with polymorphic assemblies of up to 15 subunits from 29 genes. The evolutionarily conserved BRG1/BRM, BAF47, and BAF155/BAF170 form a stable complex that carries out essential chromatin remodeling activity and therefore have been regarded as the core components of BAF complex. Here, we first confirmed that SWIRM domain of BAF155 is responsible for its interaction with BAF47 and then narrowed down the SWIRM-binding region in BAF47 to the Repeat 1 (RPT1) domain. We further presented the high-resolution crystal structure of SWIRM/RPT1 complex. Extensive mutagenesis experiments together with isothermal titration calorimetry and NMR titrations were performed to corroborate the interactions observed in crystal structure. Overall, we demonstrated that BAF155 SWIRM is a modular domain involved in BAF47 interaction, which is functionally distinct from other characterized SWIRM domains that possess DNA binding activity. Graphical Abstract: Highlights: BAF155 SWIRM domain directly interacts with the BAF47 RPT1 domain. BAF47 RPT1 domain has a novel structural fold. BAF155 SWIRM domain mediates protein–protein interactions, which is different from other canonical SWIRM domains with DNA binding activity.